Role of growth differentiation factor-15 (GDF-15) in missed miscarriage and its relationship to oxidative stress markers - Olga G. Tishkova; Lyudmila V. Dikareva; Kristina M. Romanenko (IP Berlin A.V., 2023)
Aim. The study aimed to investigate the level of growth differentiation factor-15 (GDF-15) and its relationship to markers of oxidative stress (OS) as predictors of missed miscarriage (MM). Materials and methods. A prospective cohort study of 80 females was conducted. The main group included 40 patients with MM at 5-9 weeks of gestation; the control group included 40 females with elective termination at the same gestation period. OS markers, including malonic dialdehyde, carbonyl groups of proteins, and the superoxide dismutase antioxidant enzyme, as well as the GDF-15, were measured in serum, aspiration fluid, and chorionic tissues in women with normal pregnancy and MM at 5-9 weeks of gestation. Results. The results showed that the complex balance maintained between the production of reactive oxygen species and antioxidant activity in MM is shifted towards oxidative reactions (p0.05) and is associated with non-enzymatic lipid peroxidation, and OS can become a leading factor in the pathogenesis of MM. The GDF-15 levels were significantly higher in aspiration fluid and chorionic tissues in patients of the study groups; low concentrations of GDF-15 in MM patients in aspiration fluid and chorionic tissues highlight the role of this protein as an important regulator of proinflammatory molecules (p0.05). In addition, a decrease in the GDF-15 level negatively correlates with OS markers, such as malonic dialdehyde and the superoxide dismutase antioxidant enzyme, suggesting the role of this cytokine in peroxidation and OS development. Conclusion. The study of biomarkers of independent pathological pathways as predictors of miscarriage will allow clinicians to stratify and predict the risks of early reproductive loss more accurately.